Improving parking attendants' competency to develop professional staff in the parking sector - Arief Novianto; Ahmad Basuki; Agus Siswono (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The increasing number of vehicles every year requires parking attendants who are professional and competent in managing the entry and exit of vehicles in the parking lot so as not to impede traffic. Aside from having enough parking space, a dependable parking attendant is also required to handle parking effectively. The biggest issue with this community service is a lack of awareness about parking arrangements and safe parking. This Community Service was held in collaboration with the Tulungagung Regency Transportation Service. The purpose of this activity is to develop competent professional staff in the parking sector by increasing knowledge, understanding, and abilities. The methods used in this activity are lectures, presentations, interactive questions, and answers, providing case examples and practice. From the results of the training carried out, there was an increase in the value of parking attendants' knowledge about safe parking by 31.41%. This shows that the material provided during the training can be accepted and applied well by the participants. It is envisaged that this activity will be carried out on a regular and continuous basis, allowing Tulungagung Regency parking attendants to keep their competence.